Chest wall stretching exercise as an adjunct modality in post operative pulmonary management. - M.Vikram,; Joseph H.Leonard,; K.Kamaria, (Department of Surgery, UKM Medical Centre, 2012)
Emphysematous pyelonephritis is a form of infection of the kidney. Chest physiotherapy was executed on a 15-year-old girl who had complications such as secretion retention and pleural effusion following percutaneous pigtail nephrostomy in addition to oxygen therapy and medical management to promote respiratory functions. The processes to increase chest wall mobility includes particular passive stretching and mobilization. Chest mobility exercises composed of an intercostal stretch on a determined intercostal space using index fingers, thoracic rotation and anterior compression with stretching in sitting position to improve respiratory functions. These exercises were suggested to the patient as a regular daily treatment along with low-level incentive spirometry breathing exercises. Following 9th sessions of treatment patient demonstrated satisfactory improvement by means of increasing in chest expansion and reduction in dyspnea level without using supplemental oxygen. The results expressed a substantial clinical improvement in reduction of dyspnea level and improvement in chest expansion.